PROSPECTIVE COHORT STUDY COMPARING PERITUMORAL INJECTION OF METHYLENE BLUE DYE WITH PERI-AREOLAR INJECTION AS A SINGLE APPROACH FOR THE IDENTIFICATION OF SENTINEL LYMPH NODES IN INDIVIDUALS WITH CLINICALLY NON-PALPABLE BREAST CANCER AT IGIMS, PATNA, INDIA - Kumar, Kaushalendra; Sah, Sujit Kumar; Raj, Ankit; Jha, Pawan Kumar (Student’s Journal of Health Research Africa, 2024)
Background: Selecting the optimal place for injecting the blue dye in breast cancer is one of the most hotly contested questions in the SLN detection procedure. Objective: In contrast to combining peri-areolar and peritumoral injection techniques, the study’s objective is to assess the SLN’s detection rate utilizing the peri-areolar injection technique. Methods: This prospective cohort comparative study included 60 female patients with early-stage, non-palpable breast cancer confirmed by histopathology. After essential workups like blood tests, ECGs, and chest X-rays, patients consented and were randomly assigned to two groups for methylene blue dye injections for sentinel lymph node biopsy. Results: The study compared sentinel lymph node (SLN) detection using periareolar and combined periareolar-peritumoral methylene blue dye injections. SLN detection rates were 73.3% in Group A (periareolar only) and 80% in Group B (combined technique), with no significant difference between the groups (p = 1.00). This suggests that adding peritumoral injections does not improve SLN identification over periareolar injections alone. The study also found the upper quadrant as the most common tumor site, occurring in 46.67% of Group A and 60% of Group B, demonstrating the effectiveness of methylene blue dye across different breast tumor locations. Conclusion: The study confirmed that 1% Methylene Blue Dye (MBD) is effective for Sentinel Node Biopsy (SNB) in breast cancer, suitable even in limited access settings. It showed that tumor size and grade are key factors in SLNB, with negative lymph nodes leading to better patient outcomes by avoiding axillary clearance morbidity. Additionally, the SLN detection rates were similar between periareolar and peritumoral injection techniques using MBD. Recommendation: For Sentinel Lymph Node Biopsy in early-stage breast cancer, it is advised to standardize the use of the periareolar injection technique with 1% Methylene Blue Dye.